Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1177/1744629514564584
|View full text |Cite
|
Sign up to set email alerts
|

The impact of four family support programmes for people with a disability in Ireland

Abstract: Whilst outcomes were overwhelmingly positive, further follow-up would be required to ascertain if sustained capacity building took place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Social support has been described as one of the most important protective factors for maintaining the health and well-being of parents of children with ID: It has been found that those who received formal or informal support were less stressed, more optimistic, and manifested increased levels of well-being and satisfaction with life [56,77,[89][90][91][92]. Thus, support programs or social networks for parents and their child with ID can improve family quality of life and help achieve multiple benefits both at the interpersonal and intraindividual levels [93,94]. In this sense, Bray, Carter, Sanders, Blake, and Keegan [95], found that the use of peer support programs by parents with children with ID, reduced the levels of psychological distress these parents suffered and strengthened their ability to cope with bringing up the child.…”
Section: Discussionmentioning
confidence: 99%
“…Social support has been described as one of the most important protective factors for maintaining the health and well-being of parents of children with ID: It has been found that those who received formal or informal support were less stressed, more optimistic, and manifested increased levels of well-being and satisfaction with life [56,77,[89][90][91][92]. Thus, support programs or social networks for parents and their child with ID can improve family quality of life and help achieve multiple benefits both at the interpersonal and intraindividual levels [93,94]. In this sense, Bray, Carter, Sanders, Blake, and Keegan [95], found that the use of peer support programs by parents with children with ID, reduced the levels of psychological distress these parents suffered and strengthened their ability to cope with bringing up the child.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the multi-modal engagement strategies on offer to parents meant they could dip in and out of engagement as the pressures of their family life allowed and using a variety of mediums. As described by Daly et al (2015), the opportunity to connect with others in similar circumstances builds a sense of belonging, shared identity, mutual support and in some cases, friendship. Some mothers in our study engaged mainly via Facebook, others preferred the face-to-face social activities and training opportunities, and some engaged across all the mediums.…”
Section: Discussionmentioning
confidence: 99%
“…Social support is consistently cited as a vital aspect of resilience for families with a member with intellectual disability (Cuzzocrea et al, 2016; Daly et al, 2015; Grant et al, 2007; McConnell and Savage, 2015; Peer and Hillman, 2014). Studies show that family members who receive both informal support from social networks and formal support from service providers and healthcare professionals are more likely to report positive coping strategies and greater resilience than those who receive only one form of support (Meadan et al, 2010; Peer and Hillman, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Οι παράγοντες όμως αυτοί μπορούν να έχουν επιρροή στα βραχυπρόθεσμα όπως και στα μακροπρόθεσμα αποτελέσματα μίας θεραπείας(Karst & Van Hecke, 2012). Η συμμετοχή των γονέων σε προγράμματα θεραπείας στην Ιρλανδία ενίσχυσε τη γνώση και τις δυνατότητες των οικογενειών, καθώς μπορούσαν να βοηθήσουν το μέλος της οικογένειας με ΔΑΦ αποτελεσματικότερα και να βελτιωθεί η αλληλεπίδραση τους(Daly, Sharek, DeVries, McBennett, & Higgins, 2015). Οι υπηρεσίες που είναι προσαρμοσμένες για να ικανοποιήσουν καλύτερα τις οικογενειακές ανάγκες, θα μπορούσαν να βελτιώσουν την ποιότητα ζωής των οικογενειών.…”
unclassified